The Effects of TMR® Fab 6 on Hamstring Flexibility in Healthy Subjects; An Exploratory Observational Investigation - Patterson, Richard D.; Zettlemoyer, Alexander; Plackowski, Mary; Baker, Russell; Cheatham, Scott W.; Nasypany, Alan (International journal of sports physical therapy, 2024)
Stretching programs are designed to improve hamstring flexibility by attempting to mechanically increase the length of the target tissue. However, other manual treatment approaches such as those utilized in Total Motion Release (TMR®), could be beneficial by identifying body asymmetries to assess and treat soft tissue impairments leading to diminished extensibility. The purpose of this study was to determine the effectiveness of the TMR® Fab 6 assessment and treatment to increase hamstring flexibility in healthy participants following one session of TMR®. Observational Cohort study. A convenience sample of 20 healthy participants (10 males, 10 females) were recruited from three institutions. Following collection of demographic information and a brief medical history, each participant performed a five minute warm-up on the stationary bike at a moderate intensity (80-90 RPMs) followed immediately by the bilateral performance of the Active Knee Extension Test (AKET) and Passive Straight Leg Raise (PSLR) to assess hamstring muscle length. Participants were randomly placed in the TMR® or control group. The TMR® group completed the "Fab 6" evaluation and treatment, while the control group performed one repetition of standing active hip flexion every 30-seconds for 15-minutes with both knees in full extension. Upon completion of treatment, control and TMR® groups were immediately re-evaluated on the AKET and the PSLR in the same order and fashion as baseline testing. Participants were asked to return in 24-hours for the same objective measurements as previously described. A significant time by group interaction was identified across all variables (p ≤ 0.001) for AKET and PSLR except the PSLR preferred leg from post-treatment to 24hr follow-up. The most significant increase in the AKET occurred in the TMR® group between baseline and post-treatment of the non-preferred leg (12.15°±2.94) when compared to the control group (7.15°±1.56). The results of the study suggest that implementing a regionally interdependent treatment approach like TMR® results in significant improvements in hamstring extensibility and hip ROM compared to the control group. 3.